Model Pembelajaran Terpadu Pada Mata Pelajaran PKN, IPS, Dan Bahasa Indonesia Dengan Tipe Webbed (Suatu Kajian untuk Mewujudkan Pembelajaran Bermakna Pada Siswa Kelas V Sekolah Dasar) - Listyaningsih, (Pendidikan Sekolah Dasar, 2010)
In primary school especially for the first grade, second and third the type webbed integrated learning are very appropriate to be applied. Because  for the students in that level still examine all the things in a holistics. The separated learning will cause the students undeveloped their holistic thinking. But it is possible to apply this model for the forth, fifth, and sixth grade because school teachers mean class teachers. the type webbed integrated learning, the teaching process will be more meaningful because students are not only master the lessons concepts but also reveal their ideas, critical thinking, creative, solve a problem even take a decision. Thats why through this the type webbed integrated learning, in the teaching process is expected that the students can get some experiences, as in cognitive aspect, affective also psychomotor. So, the teaching will be more meaningful